Disciplinary Problems as Perceived by the Teachers in Batuhan East and Nicolas Danao Elementary Schools - Verano, Rosanna (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study assessed the disciplinary problems perceived by teachers in Batuhan East Elementary School and Nicolas Danao Elementary School in Barangay Batuhan, Masbate City. It aimed to determine the causes of disciplinary problems, the assertive discipline strategies used by teachers, the effective ways of dealing with behavioral concerns, the disciplinary interventions implemented, and whether teachers’ perceptions differed across the two schools. The study was anchored on Piaget’s Cognitive Development Theory, Erikson’s Psychosocial Development Theory, and Kohlberg’s Moral Development Theory. A descriptive research design was employed. Data were gathered through a survey questionnaire with a rating scale, supported by informal interviews and observations. The respondents consisted of 18 teaching and non-teaching personnel from the two selected public elementary schools, and total enumeration was used. Findings showed that the causes of disciplinary problems were generally perceived as less serious, with unfavorable physical learning environment, students’ varied backgrounds, and poor lighting and ventilation identified as the leading concerns. Teachers agreed on the use of assertive discipline strategies, particularly cooperative learning, team learning, peer tutoring, and group projects. Effective ways of dealing with disciplinary problems included merits and demerits, private conferences, dialogue, verbal reinforcement, and other supportive approaches. Disciplinary interventions such as tangible recognition, home contingency or parental involvement, teacher reactions, and group contingency were generally perceived as effective. The study further revealed no significant difference in the perceptions of respondents from the two schools. The study concluded that disciplinary problems were manageable and that teachers commonly applied positive and constructive strategies aligned with child protection policies. It recommended continuous policy review, sustained use of varied discipline strategies, reinforcement of good manners and right conduct, wider dissemination of findings, and further related studies. The study is relevant to SDG 4 (Quality Education) and SDG 16 (Peace, Justice and Strong Institutions) because it supports safe, inclusive, and rights-based school discipline. Its sustainability impact lies in strengthening educational and institutional sustainability through improved classroom management, policy compliance, and school-community cooperation.